Common problems in the statistical analysis of the agronomic information. - Alemán, Freddy (2006)
Some of the most common problems in the agricultural information analysis are discussed. The correct form to utilize the factorial experiment analysis and the alternatives to substitute multiple comparisons are emphasized. The role played by the multiple comparisons on the agronomic research is reviewed giving valuable options to improve the obtained information. Inconsistencies obtained from quantitative treatments are also discussed. Recommendations about the correct form to analyze and interpret information are given.